The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3897/bdj.5.e20044
|View full text |Cite
|
Sign up to set email alerts
|

Structure and tree species composition in different habitats of savanna used by indigenous people in the Northern Brazilian Amazon

Abstract: BackgroundWoody plant diversity from the Amazonian savannas has been poorly quantified. In order to improve the knowledge on wood plants of these regional ecosystems, a tree inventory was carried out in four different habitats used by indigenous people living in the savanna areas of the Northern Brazilian Amazon. The habitats were divided into two types (or groups) of vegetation formations: forest (riparian forest, forest island, and buritizal = Mauritia palm formation) and non-forest (typical savanna). The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
(10 reference statements)
2
3
0
Order By: Relevance
“…In case of restoration post disturbance, plant actively grow through production and differentiations new aerial organs as multiple stems (Zida et al, 2009) in juvenile to tree transition and become established as adult trees. Our results agree with previous studies carried out in dry and humid environments (Oliveira et al, 2017;Astri et al, 2020). Oliveira et al (2017) had indicated that in forest and non-forest environments, more individuals are distributed in the minor diameter classes while few individuals are found in the major diameter classes and Astri et al (2020) reported that small sized trees were positively connected with great AGB in savannah system.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In case of restoration post disturbance, plant actively grow through production and differentiations new aerial organs as multiple stems (Zida et al, 2009) in juvenile to tree transition and become established as adult trees. Our results agree with previous studies carried out in dry and humid environments (Oliveira et al, 2017;Astri et al, 2020). Oliveira et al (2017) had indicated that in forest and non-forest environments, more individuals are distributed in the minor diameter classes while few individuals are found in the major diameter classes and Astri et al (2020) reported that small sized trees were positively connected with great AGB in savannah system.…”
Section: Discussionsupporting
confidence: 94%
“…Our results agree with previous studies carried out in dry and humid environments (Oliveira et al, 2017;Astri et al, 2020). Oliveira et al (2017) had indicated that in forest and non-forest environments, more individuals are distributed in the minor diameter classes while few individuals are found in the major diameter classes and Astri et al (2020) reported that small sized trees were positively connected with great AGB in savannah system. But, according to these last authors, the contri-S. Traoré et al DOI: 10.4236/ojf.2022.121003 55 Open Journal of Forestry butions of small sized trees to basal area and stem density were significantly different between vegetation types.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…One such area is the State of Roraima, located in the northern part of the Brazilian Amazonia. This ~225,000 km 2 area contains ecotone forest zones of great geoecological importance because they are located between Guiana Shield (highland savannas and tropical dry forests) and Central Amazonia (lowland tropical forests) (Barbosa and Bacelar-Lima 2008, Oliveira et al 2017), which gives them a unique phytogeographical and ecoevolutionary history, where a high degree of endemism is observed and unique vegetation sets exist (Nascimento and Proctor 1997, Milliken and Ratter 1998). However, the region has received few forest inventories and floristic surveys (Suppl.…”
Section: Introductionmentioning
confidence: 99%
“…The trees used in this PhD thesis were birch tree and ash tree. Although birch tree and ash tree are hardwood, they have different chemical composition (Kizha, 2008;ODE, 2003;Oliveira et al, 2017;Wittmann et al, 2008;WoodDatabase, 2020). Studies regarding the effect of different wood types on degradation are rare, especially in mixed culture.…”
Section: Effect Of Temperature On Biological Wood Oxidation (Chapter 5)mentioning
confidence: 99%